Dementia, Preclinical Studies in Neurodegeneration and its Potential for Translational Medicine in South America - Cardona-Gómez, Gloria Patricia; Lopera, Francisco (Frontiers in Aging Neuroscience, 2016)
Latin-American people with dementia will increase in a 368% in 2050, higher than USA and Europe. In addition, to sporadic dementia type Alzheimer and vascular dementia progression after Cerebrovascular disease, the statistics are increased in Colombia by specific populations affected with pure neurodegenerative and vascular dementias like autosomical dominant familial Alzheimer´s disease and CADASIL. In spite of the enormous human and economical effort and investment, neither sporadic nor genetic kinds of dementia progression have been prevented or blocked yet. Currently, exist several animal models that partially solve the understanding of the neurodegenerative etiopathogenesis and its treatment. However, when the potential therapies are translated to humans, those do not work or present a limited action. Main difficulties are the diverse comorbility associated to the cause and/or several affected brain regions, reducing the efficacy of some therapies which are limited to a tissue-specific action or modulating a kind of neurotransmission. Global investigation suggests that a general prevention could be achieved with the improvement in the quality of lifestyle, including healthy diet, physical and mental activity, and avoiding mechanical or chemical pro-inflammatory events in an early stage in the most of non-communicable diseases. In this review, we present some molecular targets and preclinical studies in animal models to propose strategies that could be useful in a future translation to prevent or block neurodegeneration: One is gene therapy silencing pathogenic genes in critical brain areas where excitotoxicity arise and spread. Another is to take advantage of the natural source and its wide biodiversity of natural products some of them identified by the blocking and prevention of neurodegeneration. On the other side, the casuistic of pure dementias in the Latin-American region give an exceptional opportunity to understand the pathogenesis in these human populations, and go to favour of the basic and clinical researchers interaction for a better understanding and medical care of mix dementias, which have more complex factors than pure ones. However, to promove the translation of any therapeutical alternative is neccesary to clarify the normative and protocols for developing clinical trials with original candidates or strategies proposed from South-American countries.